2010
DOI: 10.1142/s0219525910002840
|View full text |Cite
|
Sign up to set email alerts
|

Eigenvector Localization as a Tool to Study Small Communities in Online Social Networks

Abstract: We present and discuss a mathematical procedure for identification of small "communities" or segments within large bipartite networks. The procedure is based on spectral analysis of the matrix encoding network structure. The principal tool here is localization of eigenvectors of the matrix, by means of which the relevant network segments become visible. We exemplified our approach by analyzing the data related to product reviewing on Amazon.com. We found several segments, a kind of hybrid communities of densel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 85 publications
2
14
0
Order By: Relevance
“…The ratio L/N is, for all three sizes, L/N ≃ 20. As we have already shown in [46], the degree distribution is power-law on both the A and B sides, P > A,B (k) ∼ k −γA,B , but the exponents slightly differ: we found γ A ≃ 1.2 and γ B ≃ 1.35. The density of eigenvalues is shown in Fig.…”
Section: Empirical Studysupporting
confidence: 75%
See 3 more Smart Citations
“…The ratio L/N is, for all three sizes, L/N ≃ 20. As we have already shown in [46], the degree distribution is power-law on both the A and B sides, P > A,B (k) ∼ k −γA,B , but the exponents slightly differ: we found γ A ≃ 1.2 and γ B ≃ 1.35. The density of eigenvalues is shown in Fig.…”
Section: Empirical Studysupporting
confidence: 75%
“…As a complement to the study of artificial bipartite graphs, we analyzed also one empirical bipartite graph, namely the network of reviewers and items on the amazon.com server. In our previous study [46] we observed the scale-free nature of this graph and by extracting the most localized eigenvectors we found small communities with sensible semantic information. Here we wanted to check if the model of Goh et al is useful also in describing the spectra of the graphs and properties of its eigenvectors.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Here we concentrate on social networks which emerge without explicit intention of the agents. We recently investigated the properties of a hybrid human-inanimate network composed of books, reviews and reviewers in the Amazon.com site [17]. The users do not interact directly through links as "friends" or "I like", but through the products of common interest.…”
Section: Introductionmentioning
confidence: 99%